Inter-relatedness of performance between KLSE composite index and major indices / Dalila Daud - Daud, Dalila (2002)
The objective of this study is to identify whether there is a significant relationship between KLSE CI and five other indices which are Hang Seng Index (Hong Kong), Australia All Ordinaries Index (Australia), Dow Jones Industrial Average Index (USA), Financial Times-100 Index (UK) and Nikkei-225 (Japan). The study covers the period of 1st January 1990 to 31st May 2002, with special focus on the period before the economic crisis (1st January 1990- 30th June 1997), during the crisis (1st July 1997- 31st January 1998) and after economic crisis (1st February 1998- 31st May 2002). The tests were conducted using the correlation and regression analyses. It was found that there is a relationship between KLSE CI and other indices. Before the economic crisis, the foreign indices have a slight impact on the CI, however, during the economic crisis, only Hang Seng and All Ordinaries indices showed a relationship on Composite Index whilst after the economic crisis apart from those two, Nikkei Index showed a relationship as well. On the whole, it was found that the index that has the most impact is Hang Seng Index. The result also shows that there is no significant difference between the average daily changes in indices of Malaysian market and other foreign markets.